A column generation approach for the maximal covering location problem - Pereira, Marcos Antonio [UNESP]; Lorena, Luiz Antonio Nogueira; Senne, Edson Luiz França [UNESP] (Wiley, 2007)
This article presents a column generation algorithm to calculate new improved lower bounds to the solution of maximal covering location problems formulated as a p-median problem. This reformulation leads to instances that are difficult for column generation methods. The traditional column generation method is compared with the new approach, where the reduced cost criterion used at the column selection is modified by a Lagrangean/surrogate multiplier. The efficiency of the new approach is tested with real data, where computational tests were conducted and showed the impact of sparsity and degeneracy on column generation-based methods. © 2017 Wiley. All rights reserved.
Keywords: Column generation; Facility location; Lagrangean/surrogate relaxation